Analisis Korelasi Kunjungan Berobat dengan Kepuasa Pasien RS. Moedjito Dalam Metode Balanced Scorecard - Sa'adah, Lailatus; Maksum, Moh Ja'far Sodiq (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2018)
ABSTRACT The research is aimed to 1) To know the satisfaction of consumer / patient on inpatient and outpatient installation. 2) To know consumer / patient retention on inpatient and outpatient installation. 3) To analyze the relationship between the length of back treatment with consumer satisfaction / patient on inpatient installation. 4) To analyze the relationship between the length of back treatment with customer / patient satisfaction on the outpatient installation. The results showed that the level of patient satisfaction at inpatient and outpatient installation described in six indicator of satisfaction of majority have good patient satisfaction. The result of the measurement of profitability indicates there is a decrease in the level of consumer benefits this condition is less good for hospital management. There was an increase in retention in ambulatory and IGD installations while hospitalization and use of operating rooms decreased. Increased acquisition of inpatient installation and use of operating room while outpatient and IGD decreased. The result of cross tabulation and symmetric measure on hospitalization have correlation value 0,084 with significance level 0,331 significance value is above 0,05 then Ho accepted H1 is rejected this show that there is no relation between duration of treatment with inpatient satisfaction. While cross tabulation and symmetric measure on outpatient have correlation value equal to 0,122 with significance level 0,256 value significance is above 0,05 then Ho accepted H1 rejected this show that there is no relation between long treatment with outpatient satisfaction Keywords: Perspective of consumer satisfaction, Balanced Scorecard